The Retreat - Soriano, Yeyet ([Place of publication not identified] [Publisher not identified], 2016)
What would you be willing to do to secure a publication deal of a lifetime from the biggest publisher in the country?

The challenge: You have to write a true-to-life crime story set in the Philippines. The case should not be completely resolved. At least 75 percent of the manuscript needs to be completed within thirty days. You have to be willing to go on a week-long writers’ retreat in an undisclosed location to discuss your manuscript and be critiqued by the other participants. Afterward, you have to be ready to revise and edit the manuscript for final publication.

The prize: Enough money to retire and just write with a guaranteed platform for release locally and internationally.

The catch: You can’t breathe a word to anyone. Post anything on social media and you are out. You will be asked to sign a nondisclosure agreement and a release that removes any responsibility from the organizers should anything untoward happens to you. You will not be allowed to bring any gadgets to the retreat. You will be completely cut off.

So . . . are you game? -- Back cover.
Independently published.
Keywords: Philippine fiction (English); Crime in literature